Analog and digital image quality - Sardo, Alberto (Radiology and oncology (Ljubljana), 2004)
Background. Lastly the X ray facilities are moving to a slow, but continuous process of digitalization. The dry laser printers allow hardcopy images with optimum resolution and contrast for all the modalities. In breast imaging, thedelay of digitalization depends to the high cost of digital systems and, attimes, to the doubts of the diagnostic accuracy of reading the breast digital images. Conclusions. The Screen film mammography (SFM) is the most efficient diagnostic modality to detect the breast cancer in early stage and with reasonable cost. The digital mammography (DM) with the independent capturing, displaying, processing, printing and archiving phases, makes possible an optimisation of the image guality for each, single phase, assuringa satisfactory diagnosis.
Keywords: diagnostika; dojke; Mammography; Mamografija; Radiografska slika, povečanje; Radiographic Image Enhancement; rak (medicina); Rentgenski film; Rentgensko ozjačevanje zaslonov; X-Ray Film; X-Ray Intensifying Screens